Cardiac achalasia: modern concepts on etiology, pathogenesis, clinical presentation and diagnostics - Yu. V. Yevsyutina; O. A. Storonova; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present up-to-date data on etiology, pathogenesis, clinical presentation and diagnostics of cardiac achalasia.Key points. Cardiac achalasia represents primary esophageal motor disease with involvement of myenteric plexus. Basic symptoms of achalasia include dysphagia, regurgitation, chest pain and weight loss. Esophageal manometry which allows to evaluate resting pressure and relaxation phenomenon of the lower esophageal sphincter and peristaltic activity of distal part of the esophagus is the «gold standard» of diagnostics. Genetic, autoimmune and infectious theories are considered for disease etiology.Conclusion. For the present moment pathogenesis, clinical presentation and diagnostics methods of cardiac achalasia are investigated in detail, however etiology of disease remains unknown, despite of centuries-old history. The major attention is drawn to autoimmune theory which requires further investigations.